2003
DOI: 10.1099/mic.0.25783-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Streptococcus agalactiae ClpP serine protease in heat-induced stress defence and growth arrest

Abstract: The main causes of microbial death after heat exposure are not well understood. Here, it is shown that the heat-shock protein ClpP plays a major role in heat-induced growth arrest in Streptococcus agalactiae. A mutant lacking the ClpP protease was more sensitive to the inhibitory effects of heat, salt and oxidative stress than the isogenic wild-type strain. During growth arrest, this mutant displayed important modifications of its total protein content, including a decreased level of essential metabolic enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The cotranscription of clpP and upp was later confirmed by RT-PCR analysis. Previous studies on clpP gene expression in other gram-positive bacteria, including streptococci, have shown that clpP transcription is monocistronic and that the length of its product correlates with the length of the smaller transcript observed here (19,23,33,38,43,49). It is very surprising to see that the cotranscription of the clpP gene with upp is observed only in S. mutans, since the upp locus is topologically linked to the clpP locus in all streptococci.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…The cotranscription of clpP and upp was later confirmed by RT-PCR analysis. Previous studies on clpP gene expression in other gram-positive bacteria, including streptococci, have shown that clpP transcription is monocistronic and that the length of its product correlates with the length of the smaller transcript observed here (19,23,33,38,43,49). It is very surprising to see that the cotranscription of the clpP gene with upp is observed only in S. mutans, since the upp locus is topologically linked to the clpP locus in all streptococci.…”
Section: Discussionmentioning
confidence: 50%
“…In low-GϩC-content gram-positive bacteria, such as streptococci, the intracellular protease ClpP plays important roles in many cellular processes, including stress resistance, biofilm formation, and pathogenesis (12,18,31,33,38,43,49). Although, the importance of ClpP in various biological processes is well documented, regulation of its expression has not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While it thus might be expected that Clp protease mutations would usually be highly pleiotropic, the most prominent phenotype associated with loss of ClpP varies from one species to another. Thus, for example, clpP mutants of a number of low-GC gram-positive species have reduced thermo-tolerance (7,11,20,28,29,35). A loss of virulence is the most prominent phenotypic effect of mutation of ClpP in Staphylococcus aureus (8), while in Salmonella, altered expression of flagellar operons is a major effect (43).…”
mentioning
confidence: 99%